Expression of Cyr61 in ApoE−/− mice with chronic unilateral renal artery ligation - Alokkumar S. Pathak (Nature Portfolio, 2021)
Abstract Cyr61 is a member of the CCN family of proteins that is expressed in atherosclerotic lesions and regulated by angiotensin II. It is unknown whether renal artery stenosis (RAS) increases Cyr61 expression. Male ApoE−/− mice were randomized to surgically induced RAS, RAS + treatment with either irbesartan, aliskiren or amlodipine or sham-surgery. RAS resulted in increased plasma angiotensin II levels, a mild, sustained increase in systolic blood pressure and increased aortic lipid deposition compared to sham-surgery. Surgically induced RAS led to the formation of atheroma in the infrarenal aorta and there was consistent and intense staining for Cyr61 within the atheroma. Treatment with irbesartan, aliskiren and amlodipine were associated with decreased aortic lipid deposition and decreased staining for Cyr61 in aortic atheroma. Serum levels of Cyr61 were not increased in mice or humans with RAS. In summary, Cyr61 expression in aortic atheroma but not serum is increased by RAS in ApoE−/− mice and is reduced by agents that lower blood pressure.